Rimpu Culture In Mbojo Tribe Consumer Behavior In The West Nusa Tenggara Province - Mulyadin, Sri Ernawati, (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2019)
Culture is a complex symbol and fact created by humans passed down from generation to generation as a determinant and regulator of human behavior in existing societies. Researcher was interested in researching the Rimpu Cultural Phenomenon influencing Consumer Behavior in the Mbojo tribe community in West Nusa Tenggara. The study was conducted in Mbojo Tribe which included three regional governments, namely Bima City, Bima and Dompu Districts, with the object of research being the Mbojo tribe who bought Bima's unique sarong to be used as Rimpu. Data collection techniques used in this study, namely (a) Qutionary, (b) Observation, (c) Literature study. Research Variable Measurements using likes scale by spreading questionnaire to 100 people,Ã‚Â Analysis of data using multiple linear .The results show that Cultural variable, Sub Culture variable and Social Class Variables has an influence on consumer behavior of the Mbojo Tribe in West Nusa Tenggara Province.